Social marketing theory development goals: an agenda to drive change. Issue 1 (2nd January 2019) - Rundle-Thiele, Sharyn; David, Patricia; Willmott, Taylor; Pang, Bo; Eagle, Lynne; Hay, Rachel
ABSTRACT: Environmental, health, and social change is complex and frequently is framed as a problem(s) to be solved. This framing focuses effort on delivery of solutions designed to change systemic environmental, health, and social problems. Theory, an organising framework for effort, remains under-utilised in behavioural and social sciences. An individual psychological lens dominates and emphasis is placed on explaining and predicting individual behaviour and not behavioural change. It is time to break free and deliver frameworks that extend focus beyond individuals to all citizens, and apply new evaluation approaches that assess individual and structural changes. Ten Social Marketing Theory Development Goals (goals) categorised in three groups: (i) research design; (ii) building social marketing theory; and (iii) methodological innovation are outlined to assist social marketers to develop new ways of thinking that will deliver the theory and evidence base needed to outline what practitioners and policy makers should do to effect change.